A highly strained Al-Al σ-bond in dianionic aluminum analog of oxirane for molecule activation - Koshino, Kota (2022)
Since aluminum is the most electropositive element among the p-block elements, the construction of molecules bearing a dianionic Al-Al σ-bond is inherently highly challenging. Herein, we report the first synthesis of a dianionic dialane(6) 2 based on the Al2O three-membered ring scaffold, namely, an aluminum analog of oxirane. The structure of 2 has been unambiguously ascertained by spectroscopic analysis as well as X-ray crystallography, and computational studies revealed that 2 bears a highly strained Al-Al σ-bond. 2 readily reacts with the unsaturated substrates such as isocyanide, ethylene, and ketone, concomitant with the cleavage of the Al-Al σ-bond under mild conditions, leading to the four- and five-membered heterocycles 3-5. Furthermore, the reaction of 2 with two molecules of benzonitrile (PhCN) furnishes a seven-membered heterocycle 6, resulting from the C-C coupling reaction of PhCN. We further delineate that 2 selectively activates an arene ring C-C bond of biphenylene, rendering a di-Al-substituted benzo[8]annulene derivative 7. Preliminary computational studies propose that the stepwise reaction mechanism involves the Al-Al σ-bond cleavage, dearomative Al-C bond formation, subsequent sigmatropic [1,3]shifts, and a pericyclic reaction.